Adalimumab effectiveness in Behçet's disease: short and long-term data from a multicenter retrospective observational study. Issue 2 (February 2017) - Vitale, Antonio; Emmi, Giacomo; Lopalco, Giuseppe; Gentileschi, Stefano; Silvestri, Elena; Fabiani, Claudia; Urban, Maria; Frediani, Bruno; Galeazzi, Mauro; Iannone, Florenzo; Rigante, Donato; Cantarini, Luca
Abstract Our aim was to evaluate the effectiveness of adalimumab (ADA) during a 24-month study period in patients affected with Behçet's disease (BD). Clinical and therapeutic data from 100 consecutive BD patients treated with ADA were retrospectively collected and statistically analyzed. At 12-week follow-up, ADA induced clinical efficacy in 81 patients, with a mean time to response of 7.63 ± 3.43 weeks; 25 (30.9 %) patients underwent a disease relapse after 22.17 ± 1.57 months, but treatment adjustments allowed a recovery of efficacy in 11 cases. At 24-month follow-up, 67/100 patients were still on ADA therapy despite concomitant treatments. No differences were identified between ADA monotherapy and co-treatment with DMARDs about efficacy (p  = 0.09), time to response (p  = 0.61), relapses (p  = 0.36), and ADA discontinuation (p  = 0.40). No differences existed in patients switched from other tumor necrosis factor (TNF)-α inhibitors about efficacy at 12 weeks (p  = 0.13) and rapidity of response (p  = 0.93) while relapses (p  = 0.01) and ADA discontinuation at 24 months (p  = 0.001) were significantly more common. Adverse events occurred in 10 patients. ADA confirmed its effectiveness in BD. Combination therapy with DMARDs seems not significantly superior to monotherapy. Frequency and time to response for ADA was not conditioned by a previous lack or loss of efficacy to other TNF-α inhibitors, but long-term loss of efficacy seemed more likely in patients switched from other anti-TNF agents.